Eating- and weight-related factors associated with depressive symptoms in emerging adulthood. (August 2016) - Rawana, Jennine S.; McPhie, Meghan L.; Hassibi, Behzad
Abstract: Research suggests that eating- and weight-related disturbances (EWRDs) are key factors associated with depressive symptoms. However, it is unclear how EWRDs, and to a greater extent body appreciation, are associated with depressive symptoms among emerging adults. This study investigated the association between EWRDs, body appreciation, and depressive symptoms among emerging adults. Female ( n = 473) and male ( n = 135) emerging adults completed measures of restrained eating, emotional eating, external eating, drive for muscularity, body appreciation, and depressive symptoms. Hierarchical multiple regression analyses, performed separately for women and men, found that restrained eating was significantly related to depressive symptoms among both genders, whereas emotional and external eating were significantly associated with depressive symptoms in women only. Body appreciation was negatively associated with depressive symptoms in both genders. The findings highlight the need for clinicians to assess for EWRDs and promote positive body appreciation among emerging adults. Highlights: Examined the link between eating- and weight-related disturbances and depression Used a sample of female and male emerging adults Eating- and weight-related disturbances are positively associated with depression. Body appreciation is negatively associated with depression.